Cyanobacterial cytotoxicity versus toxicity to brine shrimp Artemia salina - Hisem, Daniel; Hrouzek, Pavel; Tomek, Petr; Tomšíčková, Jana; Zapomělová, Eliška; Skácelová, Kateřina; Lukešová, Alena; Kopecký, Jiří (Toxicon, 2011)
Heterocytous cyanobacteria from various habitats were screened for toxicity to brine shrimp Artemia salina and the murine lymphoblastic cell line Sp/2 in order to compare these two testing models for evaluation of risk posed by cyanobacteria to human health. Methanol extracts of biomass and cultivation media were tested for toxicity and selected extracts were fractionated to determine the active fraction. We found a significant toxic effect to A. salina and to Sp/2 cells in 5.2% and 31% of studied extracts, respectively. Only 8.6% of the tested strains were highly toxic to both A. salina and the Sp/2 cell line, and only two of the tested strains were toxic to A. salina and not to the murine cell line. Therefore, it is likely that the toxic effect of cyanobacterial secondary metabolites mostly targets basal metabolic pathways present in mammal cells and so is not manifested in A. salina. We conclude that it is insufficient to monitor cytotoxicity of cyanobacteria using only the brine shrimp bioassay as was usual in the past, since cytotoxicity is a more frequent feature in cyanobacteria in comparison with toxicity to A. salina. A. salina toxicity test should not be used when estimating the possible health risk for humans. We suggest that in vitro mammal cells be used for these purposes.
Keywords: testy toxicity; Animals; mikrocystiny; Artemia; buněčné linie; Cyanobacteria Toxins; Bacterial Toxins; zvířata; toxiny kmene Cyanobacteria; Microcystins; Risk Assessment; Lymphocytes; dlouhověkost; myši; Longevity; bakteriální toxiny; lymfocyty; viabilita buněk; hodnocení rizik; mořské toxiny; Larva; sinice; Reproducibility of Results; Cell Line; Mice; Toxicity Tests; Cyanobacteria; Cell Survival; reprodukovatelnost výsledků; larva; Marine Toxins